THE BENEFITS OF ERP AND RPA INTEGRATION IN THE CONTEXT OF INDUSTRY 4.0: EFFICIENT MASTER DATA MANAGEMENT IN THE SAP SYSTEM - Andreea Măldăreanu; Andreea Gabriela Tănase; Cristian Dragoș Țurcan; Raluca-Florentina Crețu; Viorel - Costin Banța (Annals of the University of Craiova: Economic Sciences Series)
Given the constant development of technology, the digitization of processes is a crucial issue for economic entities that want to increase performance. ERP systems and RPA technologies can be used both together and separately with the aim of easing employees’ workloads, reducing the risk of human error. The objective of this paper is to present the benefits of the integrated use of these technologies. Additionally, the review on ERP and RPA literature is illustrated in the study, being supported by a concrete example regarding the automation of master data management in the ERP system - SAP, more specifically, the automatic addition of new master data. Therefore, it demonstrates how ERP and RPA integration can lead to improved workflows, representing a starting point for entities looking to digitalize.